2017
DOI: 10.1177/2325967117s00113
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Resilience Strongest Predictor of Postoperative Outcome Following an Arthroscopic Bankart Repair

Abstract: Objectives:Resilience, which is a psychometric property related to “hardiness” or the ability to respond to challenging situations, is a recognized predictor in many outcomes’ domains. This has been studied extensively in stressful situations such as military returning from deployment, serious disease, and traumatic injury. To date however, no study has assessed the role of patient resiliency with respect to surgical outcome. The purpose of this study was to assess the role of preoperative resiliency as calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Both studies confirmed a positive correlation between high resilience and positive outcomes. 14 It is possible that all of these conditions feed into each other and can play a role in both the cause and effect, causing confounding. For example, prior studies have established a link between exercise and anxiety/depression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both studies confirmed a positive correlation between high resilience and positive outcomes. 14 It is possible that all of these conditions feed into each other and can play a role in both the cause and effect, causing confounding. For example, prior studies have established a link between exercise and anxiety/depression.…”
Section: Discussionmentioning
confidence: 99%
“…Though this study cannot specifically establish a causal relationship, it is clear that there exists a relationship between emotional resilience, anxiety and depression, and PROMs, both pre- and postoperatively. Shaha et al 14 has studied resilience in shoulder surgery on 2 distinct patient population, the elderly shoulder arthroplasty and young active military shoulder instability patient. Both studies confirmed a positive correlation between high resilience and positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, psychological variables need to be incorporated into the determination of surgical candidacy. Concurrently, researchers are shifting the focus back towards protective psychological factors and the initial findings are quite promising (48)(49)(50)(51). Resiliency is one important construct that has received recent attention as a modifiable, protective factor for chronic pain, and may be addressed within surgical contexts.…”
Section: Rationale For Multidisciplinary Approaches To Painmentioning
confidence: 99%